Mineral preference in rats treated with muscimol into the lateral parabrachial nucleus - Callera, João Carlos [UNESP]; De Luca, Laurival Antonio [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier, 2020)
Injection of muscimol, a GABAA receptor agonist, into the lateral parabrachial nucleus (LPBN) induces 0.3 M NaCl intake in rats. In the present work, we investigated whether such an effect applies to hypertonic (0.3 M) mineral solutions in general or is selective to sodium solutions in a 240 min intake test. Muscimol injection (0.5 nmol/0.2 μL) compared to vehicle injection into the LPBN of adult hydrated rats produced a preferential ingestion of 0.3 M NaCl (25.3 ± 10.2 mL) followed by a 0.3 M NaHCO3 intake (11.7 ± 5.6 mL), with no significant effect on water, KCl and CaCl2 intake. Only the effect of muscimol on NaCl intake (19.0 ± 10.4 mL) persisted in cell-dehydrated rats, with hardly any effect on water or other mineral solutions. The results suggest that the LPBN controls the ingestion of hypertonic NaCl and NaHCO3. They also suggest a selective mechanisms involving the LPBN to check hypertonic sodium intake.
Keywords: Bicarbonate; Dehydration; Fluid intake; GABA; Parabrachial nucleus; Receptors; Sodium appetite